Increase in Purge Modes of the Rostov NPP Water Cooler in Connection with No. 3 and 4 Power Unit Start-Up - O. I. Gorskaya; I. V. Medulka (Глобальная ядерная безопасность)
The object of research is the cooling pond of the Rostov NPP and the dam section of the Tsimlyansk reservoir. This work carries out the development of the optimal variant of blowing the cooling pond of the Rostov NPP in a year-round mode to provide the normalization of its mineralization, while observing the environmental requirements for thermal and hydrochemical pollution of the dam section of the Tsimlyansk reservoir. The use of a modern method of numerical modeling of hydrodynamics and heat and mass transfer as well as a method for calculating salt balances based on the law of conservation of mass, made it possible to determine the most optimal mode of blowing a cooling reservoir in a year-round mode which will provide the normalization and maintenance of water salinity in the cooling reservoir with the minimum volume of its blowdown and, accordingly, the least degree of influence on the thermal and hydrochemical regimes of the near-dam section of the Tsimlyansk reservoir.